The Study of the Mineral Composition in the Granite Rocks in the Village of Lhok Pawoh, South Aceh District - Bakruddin Bakruddin; Arnold Rikardo Sihombing; Zulkarnain Jalil (Jurnal Inotera, 2020)
The potential of non-metallic mineral resources in South Aceh is very diverse, such as one of the granite rocks located in Lhok Pawoh village, Sawang subdistrict. Granite rocks have a distinctive characteristic based on its constituent minerals. The purpose of this research is to obtain information about the constituent minerals in the granite rocks of Lhok Pawoh village. The research method uses X-ray Fluorescence (XRF) technique, then the observation of surface morphology is done by Scanning Electron Microscopy (SEM). The XRF test results show that there are 14 phases of mineral identified as the constituent mineral phase, where the very dominant SiO2 mineral reaches 67.9%, then the mineral phase of Al2O3 by 15%, and the third Fe2O3 of 6.03%, and is followed by the other minor phase of minerals. As for the results of the morphological observation, the dominant element appears in several factors, namely Si, O, and Al. From the two testing and analysis methods can be concluded that the granite stone of the village Lhok Pawoh is dominated by silica elements, which can visually be seen in white.Copyright © 2018 Politeknik Aceh Selatan.